(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Diamond-like carbon (DLC) provide very excellence performance in term of friction coefficient and wear resistance under boundary lubrication. the nano characteristic of the transformed layer has not been studied in terms of its hardness which is believed to have a significant effect in the tribological performance. This study presented the scratch test of the DLC transformed layer was obtained from the AFM scratch test that governs the friction behavior of DLC. As a result, the hardness of the DLC transformed layer depends on the oil temperature, where the sliding interface of DLC softened during the friction test due to graphitization process